Recycling of Al chips and Al chips composites using high-pressure torsion - Mohamed Ibrahim Abd El Aal (Materials Research Express, 2021)
Pure Al chip, Al chip-20% Al _2 O _3 , and Al chip-20% SiC samples were recycled using high-pressure torsion (HPT). Influence of the HPT processing on the feasibility of the consolidation, the microstructure evolution, and the hardness of pure Al chip, Al chip-20% Al _2 O _3 , and Al chip-20% SiC samples was investigated and compared with those of the as-received Al and HPTed Al solid samples. The HPT processing successfully produces approximately fully dense ultrafine-grained (UFG) microstructure Al and Al composite samples with relative densities ranged from 99.7%–98.3%. Moreover, HPTed recycled UFG Al chip, Al chip-20% Al _2 O _3 , and Al chip-20% SiC samples cost was lower by 11%–2678% than that of Al and Al composites samples produced using micro and nano-powders processed by HPT or powder metallurgy (PM). The HPT processing of the Al chip and Al chip composites samples effectively refine and fragmented the Al matrix and reinforcement particles, and so the hardness obviously increases.